Trench DMOS interface trap characterization by three-terminal charge pumping measurement - Izzudin , Ismah; Kamaruddin , Mohd. Hanif; Nordin, Anis Nurashikin; Soin, Norhayati (Elsevier, 2012)
The applicability of three-terminal charge pumping (3T-CP) technique to characterize the gate-oxide/Silicon (SiO2/Si) interface in a 45 nm thick SiO2, n-type trench Double-diffused Metal–Oxide–Semiconductor (DMOS) technology transistors is studied. The charge pumping current for process control monitor kerf (PCM-Kerf) structures were successfully measured during experiments. The plot shapes and trends are in agreement with previously reported work. A correlation study was performed with the numerical value of charge pumping current and experimental results on PCM-Kerf for a planar DMOS with 4 terminals. The charge pumping measurements showed very high source–drain current after approximately −2 V Vbase value.